2013
DOI: 10.1007/s11764-013-0273-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of depressive symptomatology in African-American breast cancer patients

Abstract: Purpose This study assessed the levels of depressive symptomatology in African Americans women with breast cancer compared to those of women without breast cancer and examined demographic, psychosocial, and clinical factors were correlated with depression. Methods A total of 152 African American women were recruited from Washington DC and surrounding suburbs. Breast cancer patients (n=76 cases) were recruited from a healthcare center and women without cancer were recruited from health fairs (n=76 comparison)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 65 publications
1
24
1
Order By: Relevance
“…Moreover, one study documented lower psychological well-being among younger Black BC survivors relative to older Black survivors [57]. Similarly, another study found that young Black BC survivors were more likely to report depressive symptoms than young Black women with no BC history [58]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, one study documented lower psychological well-being among younger Black BC survivors relative to older Black survivors [57]. Similarly, another study found that young Black BC survivors were more likely to report depressive symptoms than young Black women with no BC history [58]. …”
Section: Resultsmentioning
confidence: 99%
“…Compared with older Black BC survivors and young Black women without BC, young Black BC survivors reported lower physical well-being and functioning [57, 58]. Issues related to infertility and sexual dysfunction (e.g., loss of sexual desire, vaginal dryness, pain during intercourse) were reported among young Black participants in one study [56].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigators found that depression is underreported among AA-BCS. Further, measurements including self-report, used to identify depression, tend to be inadequate in identifying depressive symptomatology within this population [22][23][24]. For example, Zhang and Gary examined measurements to assess for depression and found that AA-BCS were less likely to say the word Bdepression^or discuss depressive symptoms compared to their Caucasian counterparts [22].…”
Section: Imited Survivorship Support and Educationmentioning
confidence: 99%